An economic analysis of precision viticulture, fruit, and pre-release wine pricing across three Western Australian cabernet sauvignon vineyards - Maynard, Hayley Del (Curtin University, 2015)
The effects of Precision Viticulture (PV) technologies on quality and price of fruit and wine were spatially analysed through case studies and an overarching levelised cost model. Wines made from separate vigour zones were subjected to sensory and chemistry analysis to examine the effects of vigour on organoleptic and volatile properties and ultimate price and quality. A levelised cost model analysed the break even cost of fruit production and benefits of PV adoption.